2015
DOI: 10.3390/met5020720
|View full text |Cite
|
Sign up to set email alerts
|

Production of Bulk Metallic Glasses by Severe Plastic Deformation

Abstract: The aim of this study was to show the possibility to produce bulk metallic glass with severe plastic deformation. High pressure torsion was used to consolidate Zr-based metallic glass powder and deform it further to weld the powder particles together. The produced samples were investigated with Scanning electron microscope (SEM), Transmission electron microscope (TEM), Differential scanning calorimetry (DSC) and X-ray diffraction (XRD) to check if the specimens are fully dense and have an amorphous structure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…In the present study, we investigate the influence of pressure on the formation of the ductile β-phase in γ-based TiAl alloys, which is not only of fundamental interest, but is also most relevant to modelling high-pressure deformation techniques, such as high-pressure torsion, in order to achieve severe plastic deformation [11][12][13][14][15] and high-pressure near-net-shape forging [16][17][18][19]. These deformation processes operate at pressures up to 7 GPa and forces exceeding 1 GN, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we investigate the influence of pressure on the formation of the ductile β-phase in γ-based TiAl alloys, which is not only of fundamental interest, but is also most relevant to modelling high-pressure deformation techniques, such as high-pressure torsion, in order to achieve severe plastic deformation [11][12][13][14][15] and high-pressure near-net-shape forging [16][17][18][19]. These deformation processes operate at pressures up to 7 GPa and forces exceeding 1 GN, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…To discern the origins of this variability in properties, significant experimental and theoretical efforts are currently underway to improve our understanding of the links between processing, structure and properties in BMGs [5,6,11,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Aside from these structure-property relationships, which invariably dictate the characteristics and hence performance of a material, there also appears to be a strong influence of testing conditions on the mechanical behavior of (certain) metallic glasses.…”
Section: Introductionmentioning
confidence: 99%
“…Zr-MG powder was compacted and deformed via HPT beforehand. It could be shown that fully dense and amorphous specimens without cracks and pores can be fabricated with sufficient applied strains and no crystallization occurred during the HPT process 45 .…”
Section: Introductionmentioning
confidence: 99%